'Mixing It Up': An interview with Ariel Schrag. Issue 2 (1st December 2015) - Greenbaum, Andrea
Ariel Schrag's 2014 lecture at the University of Chicago's Center for the Study of Gender and Sexuality, entitled, 'How to write anything', is emblematic of the artist herself. She is remarkably skilled in all genres, deftly moving from illustrating and writing acclaimed graphic novels like Awkward and Definition (2008), Potential (2008) and Likewise (2009), editing Stuck in the Middle (2007), writing television scripts for the L-Word and How to Make It in America, and composing her latest creation, her first novel, Adam (2014). In the following Skype interview, conducted with Andrea Greenbaum on 9 December 2014, Ariel Schrag explores Jewish identity, artistic habits, and getting 'lucky'.